Are they not Nigerians? The obligation of the state to end discriminatory practices against persons with disabilities. Issue 2 (June 2019) - Arimoro, Augustine Edobor
Nigeria has ratified several international instruments that protect the rights of, and guarantee freedom from discrimination of persons with disabilities (PWD). Despite the above, the country is yet to fully implement the appropriate measures required to achieve the objective of protecting PWD. Successive administrations since the return to civil administration in the country in 1999 have not fulfilled the mandate in the 1999 Constitution of the Federal Republic of Nigeria (as amended) dealing with disability rights. While the passing into law in January 2019 of the Discrimination Against Persons with Disabilities (Prohibition) Act 2018 is commendable, it only reflects the pressure on the Federal Government of Nigeria by disability rights advocates and PWD. This article aims to, among others, highlight the plight of PWD in Nigeria, the need to protect their rights and guarantee their freedom from discriminatory practices. To achieve this aim, a review of international and domestic instruments, as well as literature on the subject, is undertaken. The article proposes that the Nigerian government should aim towards inclusivity and accommodation of PWD. For example, instead of merely establishing special schools for PWD, there should be a design to allow for the training of teachers to meet the needs of special children in regular schools.